"I Was Raised in Addiction": Constructions of the Self and the Other in Discourses of Addiction and Recovery. (December 2020) - Sibley, Adams L.; Schalkoff, Christine A.; Richard, Emma L.; Piscalko, Hannah M.; Brook, Daniel L.; Lancaster, Kathryn E.; Miller, William C.; Go, Vivian F.
The aim of this article is to address how conceptualizations of addiction shape the lived experiences of people who use drugs (PWUDs) during the current opioid epidemic. Using a discourse analytic approach, we examine interview transcripts from 27 PWUDs in rural Appalachian Ohio. We investigate the ways in which participants talk about their substance use, what these linguistic choices reveal about their conceptions of self and other PWUDs, and how participants' discursive caches might be constrained by or defined within broader social discourses. We highlight three subject positions enacted by participants during the interviews: addict as victim of circumstance, addict as good Samaritan, and addict as motivated for change. We argue participants leverage these positions to contrast themselves with a reified addict -other whose identity carries socially ascribed characteristics of being blameworthy, immoral, callous, and complicit. We implicate these processes in the perpetuation of intragroup stigma and discuss implications for intervention.